India to use global positioning in civil air navigation system. - Singh, S. (IEEE spectrum)
In the footsteps of the United States, Europe, and Japan, Indian air authorities are undertaking the mammoth task of fielding a navigation system for civil aviation based on signals from Global Positioning System (GPS) satellites. The Satellite Based Augmentation System (SBAS) is intended to fill the gap between systems developed by the advanced industrial countries, resulting in an unbroken service for flights between Europe and the Asia-Pacific region